An investigation of the effects of programming with Scratch on the preservice IT teachers’ self‐efficacy perceptions and attitudes towards computer programming - Yukselturk, Erman; Altiok, Serhat (British journal of educational technology, 2017)
The purpose of this study was to analyze the effects of programming with Scratch on the views of preservice Information Technology (IT) teachers towards computer programming. The study sample consisted of 151 preservice IT teachers who took an elective course including a Scratch module in the 2013–14 academic year. Three online questionnaires (Personal Information Questionnaire, The Computer Programming Self‐Efficacy Scale and The Computer Programming Learning Attitude Scale) were used to gather the quantitative data and focus group interviews were conducted to collect the qualitative data regarding the preservice IT teachers’ views in more detail. According to the results, there were significant increases in the mean of the preservice IT teachers’ self‐efficacy perceptions regarding almost all complex programming tasks after their Scratch programming experience. The results also showed that the preservice IT teachers’ negative attitudes towards programming decreased significantly and programming in the Scratch platform had significantly positive effects on the preservice IT teachers’ attitudes regarding some items in the scale.